(untitled) (Journal of Information Technologies in Education (ITE), 2015)
This article is devoted to defining the forms and the required components cloud technology usage during studying of subject teachers. In order to improve the learning process it’s necessary to use such powerful technology as ‘cloud computing’. They support traditional forms of education and also are a new step in the development of education. Cloud technologies are-effective, efficient and flexible way to satisfy the needs of students during getting of new knowledge. Nowadays a characteristic feature of our time is rapid growing of using cloud technology.That is why we are spectators of implementation of cloud technologies and services in the system of higher and secondary education, too. A common information space in education using mostly cloud technologies that provide Microsoft and Google is creating now. Google Apps for Education containing free tools that allows teachers and students to communicate, teach and learn more effectively and efficiently. Significant advantage of using cloud services is providing application development and storage of large amounts of data on servers in distributed information processing centers via the Internet. That is why cloud technology is a powerful tool to activate students’ self-guidance work.Surely, growing demand for professionals who knows the technology of cloud computing will increase slowly.